2016
DOI: 10.4103/0366-6999.192788
|View full text |Cite
|
Sign up to set email alerts
|

Arthroplasty versus Internal Fixation for Displaced Intracapsular Femoral Neck Fracture in the Elderly

Abstract: Background:There is conflicting evidence as to whether the femoral head should be preserved or replaced in elderly patients with displaced intracapsular femoral neck fractures. In this article, we performed a systematic review and meta-analysis to compare the short- and long-term effectiveness of arthroplasty (AR) and internal fixation (IF).Methods:PubMed, Embase, and the Cochrane Library were searched systematically up to January 2016. All randomized controlled trials directly comparing the effectiveness of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…However, some studies believe that HA will increase the operation time and bleeding volume, bring about a higher infection rate and mortality caused by cardiovascular accidents during perioperative period [ 27 ] . Jiang et al believed that although HA does not cause a higher chance of perioperative infection, it does not improve the hip function of patients either [ 29 , 31 ]. Thus, in this study, it is necessary to conduct research on the abovementioned issues in those two treatments based on most recent literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies believe that HA will increase the operation time and bleeding volume, bring about a higher infection rate and mortality caused by cardiovascular accidents during perioperative period [ 27 ] . Jiang et al believed that although HA does not cause a higher chance of perioperative infection, it does not improve the hip function of patients either [ 29 , 31 ]. Thus, in this study, it is necessary to conduct research on the abovementioned issues in those two treatments based on most recent literature.…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that patients can exercise as early as possible after hemiarthroplasty to achieve functional recovery, and the bed rest time after internal fixation is relatively longer, resulting in untimely exercise and limited functional recovery. However, the functional weakness of the IF group became less obvious during long-term follow-up [ 29 , 31 ], which may be due to that better exercise achieved a more satisfactory functional recovery in the later period of the IF group. The literature on the EQ-5D score in this study is relatively rare, especially that there are only 3 studies in the 2-year group, and the results are mainly based on the subjective score of the patient, without no further accurate functional evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analysis studies report that replacement AP is a more suitable surgical option in patients with femur neck fracture (789). Although few studies report the more suitable option for early rehabilitation in patients with unstable intertrochanteric fracture, replacement AP vs.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the load conduction effect of the trabecular stem was better when implanted into human body and the stress distribution was more uniform. Previous studies have shown that the femoral stem is the weakest part of the hip prosthesis component under the in uence of stress concentration [21][22][23][24] . Therefore, optimizing the middle part of the stem with porous structure is reasonable for reducing stress concentration and improving life service.…”
Section: Discussionmentioning
confidence: 99%